2012
DOI: 10.1100/2012/583973
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Metaheuristic DE/CS Algorithm for UCAV Three-Dimension Path Planning

Abstract: Three-dimension path planning for uninhabited combat air vehicle (UCAV) is a complicated high-dimension optimization problem, which primarily centralizes on optimizing the flight route considering the different kinds of constrains under complicated battle field environments. A new hybrid metaheuristic differential evolution (DE) and cuckoo search (CS) algorithm is proposed to solve the UCAV three-dimension path planning problem. DE is applied to optimize the process of selecting cuckoos of the improved CS mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 16 publications
0
46
0
Order By: Relevance
“…Some studies have focused on improving LFRW [4][5][6][7][8][9][10] and BSRW [11][12][13][14][15]. Some attempts have been made to combine CS with other optimization techniques like particle swarm optimization [16,17], Tabu search [18], differential evolution [19], ant colony optimization [20], and cooperative coevolutionary framework [21,22]. The above studies have shown their contribution to the research on CS.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on improving LFRW [4][5][6][7][8][9][10] and BSRW [11][12][13][14][15]. Some attempts have been made to combine CS with other optimization techniques like particle swarm optimization [16,17], Tabu search [18], differential evolution [19], ant colony optimization [20], and cooperative coevolutionary framework [21,22]. The above studies have shown their contribution to the research on CS.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a variety of new nature-inspired metaheuristic algorithms have been reported, e.g., ant lion optimizer (ALO) [19], BA [20], biogeography-based optimization (BBO) [21,22], charged system search (CSS) [23], CS [24][25][26], animal migration optimization (AMO) [27], krill herd (KH) [28][29][30][31][32], wolf search algorithm (WSA) [33], artificial plant optimization algorithm (APOA) [34], human learning optimization (HLO) [35], swarm search [36], earthworm optimization algorithm (EWA) [37], magnetic optimization algorithm (MOA) [38], monarch butterfly optimization (MBO) [39] and others. In fact, MBO is inspired by the migration behavior of the monarch butterflies in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scholars study the path planning problem constantly. The represented techniques of UCAV path planning are like PSO [1,2], dynamic planning [3], * algorithm [4,5], ant colony algorithm [6], genetic algorithm [7,8], and so on [9][10][11][12][13]. Reference [14] discussed sparse algorithm, another effective way, which greatly improves the efficiency of the search, but it is easy to fall into a death cycle under the conditions of lacking maneuver ability.…”
Section: Introductionmentioning
confidence: 99%